NOD2-mediated dual negative regulation of inflammatory responses triggered by TLRs in the gastrointestinal tract - Masaki, Sho; Masuta, Yasuhiro; Honjo, Hajime; Kudo, Masatoshi; Watanabe, Tomohiro (Frontiers in Immunology, 2024)
Loss-of-function mutations in nucleotide-binding oligomerization domain 2 (NOD2) constitute the primary risk factors for Crohn's disease. NOD2 is an intracellular sensor for muramyl dipeptide (MDP), a small molecule derived from the peptidoglycan layer of bacterial cell wall. Although NOD2 is involved in host immune responses, much attention has been paid to the involvement of NOD2 in the maintenance of intestinal homeostasis. Despite the fact that the proinflammatory cytokine and chemokine responses induced by NOD2 activation alone are weaker than those induced by toll-like receptors (TLRs), NOD2 plays a crucial role in host defense against invading pathogens and in the regulation of immune responses. Recent studies have highlighted the importance of negative regulatory functions of NOD2 in TLRs-mediated proinflammatory cytokine responses. MDP-mediated activation of NOD2 induces interferon regulatory factor 4 (IRF4) expression, thereby suppressing nuclear factor-kB-dependent colitogenic cytokine responses through the inhibition of Lys(K)63-linked polyubiquitination on receptor-interacting serine/threonine protein kinase 2. MDP-mediated activation of NOD2 also downregulates TLR9-induced type I IFN responses by inhibiting the K63-linked polyubiquitination of TNF receptor-associated factor 3 via deubiquitinating enzyme A (DUBA) expression. Thus, NOD2 exerts dual negative regulation of TLRs-mediated proinflammatory cytokine and type I IFN responses by inducing the expression of IRF4 and DUBA, respectively. In this review, we summarize the molecular mechanisms whereby NOD2 activation suppresses TLRs-mediated proinflammatory and type I IFN responses. In addition, we discuss the clinical relevance of the NOD2-mediated negative regulation of TLRs in inflammatory bowel disease.